Pengaruh Kesadaran Wajib Pajak, Sikap Wajib Pajak atas Pelaksanaan Sanksi Denda dan Kualitas Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan (Studi Kasus Wajib Pajak Bumi dan Bangunan di Kabupaten Bantul) - Suyanto, Suyanto; Purwanti, Purwanti (Akmenika, 2016)
The purpose of this study was to examine the influence awareness of the taxpayer,the taxpayer stance on the implementation of financial penalties, and quality ofservice tax authorities on tax compliance and building earth. This research wasconducted at the Department of Revenue, Finance and Asset Management of Bantulthrough 110 respondents. The data analysis technique used is multiple linearregression technique which consists of one dependent variable is tax compliance,and three independent variables taxpayer awareness, the attitude of the taxpayer onthe implementation of financial penalties, and quality of service tax authorities. Basedon the analysis performed, it is known that the awareness of the taxpayer, thetaxpayer stance on the implementation of financial penalties, and quality of servicetax authorities simultaneously and partially on tax compliance and building earth.The predictive ability of the independent variable on the dependent variable showedindependent variables are able to explain the dependent variable variation of 33.8%and 66.2% explained by other variables.